Integrasi Manajemen Pendidikan, Deep Learning, dan AI dalam Pembelajaran Berbasis Masalah di SMK Kesehatan: Integration of Educational Management, Deep Learning, and AI in Problem-Based Learning at Health Vocational Schools - Julinda Siregar; Badriah, Ainun; Sabila Aprilia; Achmad Saifudin (Al-Gafari : Manajemen dan Pendidikan, 2025)
This study is motivated by the need to address learning challenges in vocational high schools (SMK), especially in the fields of health and science, which have not fully integrated adaptive educational management, deep learning strategies, and artificial intelligence (AI). The aim of this study is to explore the potential integration of these three elements in supporting problem-based learning (PBL). A systematic literature review method was used, analyzing 20 relevant national and international journal articles and educational reports published in the last five years. The data were analyzed using a thematic synthesis approach to identify patterns, contributions, and challenges of the integration. The findings show that the use of AI and deep learning can enhance personalized learning, provide real-time feedback, and strengthen students’ contextual problem-solving skills. On the other hand, the implementation of adaptive educational management supports the development of collaborative digital learning ecosystems. This study concludes that appropriate integration of technology and educational management in PBL at SMKs has the potential to significantly improve learning quality. However, successful implementation requires improving teacher competencies, adequate digital infrastructure, and progressive and sustainable educational policies.